Does the type of ablation device influence on the results of the treatment of atrial fibrillation in open heart surgery? - А. В. Богачев-прокофьев; С. И. Железнев; А. Н. Пивкин; С. О. Лавинюков; А. М. Караськов; И. В. Иванов (Патология кровообращения и кардиохирургия, 2015)
We analysed results of different types of monopolar and bipolar radiofrequency (RF) ablation in the surgical correction of valvular heart disease. From 2007 to 2011, RF ablation procedure performed 283 patients with atrial fibrillation and heart valve disease. Depending on the type of ablation electrode, all patients were divided into three groups: 64 (22.6%) cases monopolar ablation (MA), irrigated bipolar electrode (IBE) was used in 83 (29.3%) cases and dry bipolar ablation (DBA) formed 136 (48.1%). Time of ablation schemes using a monopolar electrode was significantly more, what increased time of aortic cross-clamping and cardiopulmonary bypass. No significant differences in the time parameters for groups of IBE and DBA has been received. Mortality in the hospital stay was not significantly different between the groups, reaching for the MA, IBE and DBA groups 1.5, 1.2 and 2.2% (p = 0.957; p = 0.784; p = 0.139). In neither case death was not directly related to the ablation procedure and type of electrode. Freedom from AF and AT in groups using bipolar ablative devices was significantly higher at all stages of the assessment results, amounting to MA, IBE and DBA groups, 68.1%, 84.0% and 85,7% respectively (log-rank test, p = 0.012 to DBA group and p = 0.021 for Group IBE). No significant differences between the use of irrigated electrodes and execution of the dry ablation were found (log-rank test, p = 0.249).